Los editores de Laura Méndez de Cuenca - Fernández, Ángel José (El Colegio de México, 2014)
This article revises the posthumous editions of the poetry of Laura Méndezde Cuenca and her editors’ work, who formed the anthologies Mariposasfurtivas (1953), Poesía rediviva (1977), La pasión a solas (1984) –andits re-editions with variants (1989 y 2003)–, and Impresiones de una mujera solas. Una antología general (2006), as well as the edition of her Poesía(2011), included in v. 2 of Laura Méndez de Cuenca. Su herencia cultural,coordinated by Mílada Bazant. The editors Gonzalo Pérez Gómez y PabloMora stand out and like them, others, like Mora´s helper, RobertoSánchez Sánchez, who was also the compiler of Laura Méndez de Cuenca.Su herencia cultural. The literary works of the mexiquense writer, withexception of her volume of short stories, had been dispersed, in particularher poetry, scattered in Mexico City’s newspapers and in those fromthe interior of the Republic; in the Peruvian, Argentinian, and Uruguayanpresses; in the Madrid, and Barcelona newspapers and even in someNorth American presses. Finally, this article specifies some inconsistenciesthat, in respect of the periodic edition, can be distinguished eitherin the anthologies or in the volume of her Poesía.